2013
DOI: 10.3111/13696998.2013.782034
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of the clinical and economic burden during hospitalizations among cancer patients with febrile neutropenia

Abstract: FN-related hospitalizations among cancer patients are costly and accompanied by considerable mortality risk. Substantial differences in the clinical and economic burden of FN exist depending on cancer types, comorbidities, and infection types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
64
4
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(76 citation statements)
references
References 30 publications
3
64
4
5
Order By: Relevance
“…By contrast, Mahmud et al reported a significantly lower incidence (25-40%) of FN in their series (31). Our high incidence of FN may be explained by the higher prevalence of underlying hematological malignancies that increase the risk for FN, as 10-50% of patients with solid tumors may develop FN, compared with 80% of those with hematological malignancies (6).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…By contrast, Mahmud et al reported a significantly lower incidence (25-40%) of FN in their series (31). Our high incidence of FN may be explained by the higher prevalence of underlying hematological malignancies that increase the risk for FN, as 10-50% of patients with solid tumors may develop FN, compared with 80% of those with hematological malignancies (6).…”
Section: Discussionmentioning
confidence: 97%
“…FN is the most frequent complication and the leading cause of morbidity and mortality in oncology patients undergoing intensive chemotherapy; it is also associated with a significant economic and social burden on the health system (6). Early recognition of FN and initiation of broad spectrum empirical systemic antibacterial therapy is crucial for avoiding progression to sepsis and possible death (7).…”
Section: Introductionmentioning
confidence: 99%
“…Premier's methodology and database, in which individualized severity-adjusted expected outcome parameters are calculated for each patient, are regularly used to evaluate mortality, costs, complications, morbidity, and resource utilization across a wide variety of patients and disease states [21,[24][25][26][27][28]. In this study, we focused on illnesses related to poisoning or toxic effects of drugs and demonstrated that inpatients primarily cared for by medical toxicologists, compared to patients primarily cared for by non-toxicologists and adjusted for predicted values, experienced significantly shorter hospital stays, generated lower costs, and suffered lower mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have estimated inhospital mortality rates up to 5-11 % among overall cancer patients admitted with febrile neutropenia [2,[6][7][8]. Certain risk factors such as the presence of hypotension, septic shock, and bacteremia among these patients may increase the risk of mortality [2,9,10].…”
mentioning
confidence: 99%